Dr. Guglielmo Rufolo — Deep Plane Facelift — Rome - Rufolo, Guglielmo (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Guglielmo Rufolo, practicing in Rome, Italy. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003172; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; italy; rome